CE: Epilepsy Update, Part 1. (May 2015) - Smith, Gigi; Wagner, Janelle L.; Edwards, Jonathan C.
Abstract : OVERVIEW: Epilepsy is a serious, common neurologic disease that affects people of all ages. As underscored in the 2012 Institute of Medicine report Epilepsy Across the Spectrum: Promoting Health and Understanding, the millions of people living with epilepsy in the United States face the challenges of seeking out high-quality, coordinated health care and community services; overcoming epilepsy misinformation and stigma; and finding understanding and support in their communities. This article, the first in a two-part series, discusses new research that has increased our understanding of epilepsy's etiology and pathophysiology, new definitions that are changing the ways we evaluate and treat this disease, conditions that frequently present with epilepsy, and psychosocial challenges faced by people with epilepsy. Part 2, which will appear in next month's issue, reviews comprehensive nursing care and evidence-based treatment for epilepsy and presents resources for people with epilepsy and their families. Abstract : This first article in a two-part series discusses new research on the causes of epilepsy, new definitions that are changing the ways we evaluate the disease, and the psychosocial challenges faced by people who have it.